Visual function and quality of life in children and adolescents with anophthalmia and microphthalmia treated with ocular prosthesis. Issue 7 (30th April 2020) - Casslén, Beatrice; Jugård, Ylva; Taha Najim, Rezhna; Odersjö, Marie; Topa, Alexandra; Andersson Grönlund, Marita
Abstract: Purpose: To evaluate health‐related quality of life (HR‐QoL), vision‐related (VR‐)QoL and perceptual visual dysfunction (PVD) among individuals with anophthalmia (A) and microphthalmia (M) treated with ocular prosthesis. Methods: The study comprised 15 individuals (mean age 6.6 years; range 1.7–14.1) with unilateral A or M. Three validated instruments measuring HR‐QoL and VR‐QoL were used: The Pediatric QoL Inventory (PedsQL), consisting of physical and psychosocial self‐report and parent‐proxy report (2–18 years); Children's Visual Function Questionnaire (CVFQ); and Effects of Youngsters' Eyesight on Quality of Life (EYE‐Q). Perceptual visual dysfunctions (PVDs) were assessed by history taking according to a specific protocol. Results: A/M children and their parents showed low HR‐QoL scores (PedsQL total score: 66.3; 69.6) compared with controls (83.0; 87.61) (p = 0.0035 and <0.0001, respectively, unpaired t ‐test). No differences were found between A/M children and parents, but parents tended to underestimate their children's emotional state. A/M children with subnormal visual acuity (VA) for age scored lower in physical health compared with A/M children with normal VA (p = 0.03, Mann–Whitney U ‐test). No significant VR‐QoL differences between A/M children and references or between A/M children with subnormal or normal VA for age were found. More A/M children than controls exhibited PVDs in ≥1 area (7/11 versus 4/118; p < 0.0001, Fisher's exact test). Conclusion: A/M individuals show poor HR‐QoL and increased PVDs. No difference in QoL was found between children and parents, though the children tended to score lower in emotional well‐being. A/M children with subnormal VA showed lower physical health score. These problems indicate the necessity of a thorough multidisciplinary assessment and follow‐up of children with A/M.